Effect of Alcoholic Extracts of Mentha Piperita Roots on Culex Pipiens Mosquitoes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study aimed to know effects of alcohol extract of Mentha piperita plant roots on larva and hatching eggs of Culex pipiens mosquitoes after exposure to different concentrations (100, 300, 500, 700, 900) mg/l from extracts. The results appeared that percentage of larva mortalities was (37, 55, 63, 72, 91) %, (10, 24, 33, 42, 76) %, (16, 28, 41, 66, 67) % and (12, 18, 20, 23, 47) % for first, second, third and fourth phases and LC50 was (280), (680), (600) and (more than 900) mg/l respectively, and percentage of hatching eggs (81, 78, 76, 73, 60) % and LC50 (more than 900) mg/l. Also, results didn’t show significant differentiation between the percentage of larva mortalities stages but showed it among the percentage of hatching eggs in the level of probability (0.05(. the concentration showed positive correlation coefficients with the percentage of mortalities and negative correlation coefficient with the percentage of hatching eggs.